Malvinas-slope water intrusions on the northern Patagonia continental shelf - Piola, Alberto Ricardo; Martínez Avellaneda, N.; Guerrero, Raul Alfredo; Jardon, Fernanda Paola; Palma, Elbio Daniel; Romero, Silvia Inés (Ocean Science)
The Patagonia continental shelf located off southeastern South America is bounded offshore by the Malvinas Current, which extends northward from northern Drake Passage (∼55deg; S) to nearly 38deg; S. The transition between relatively warm-fresh shelf waters and Subantarctic Waters from the western boundary current is characterized by a thermohaline front extending nearly 2500 km. We use satellite derived sea surface temperature, and chlorophyll-a data combined with hydrographic and surface drifter data to document the intrusions of slope waters onto the continental shelf near 41deg; S. These intrusions create vertically coherent localized negative temperature and positive salinity anomalies extending onshore about 150 km from the shelf break. The region is associated with a center of action of the first mode of non-seasonal sea surface temperature variability and also relatively high chlorophyll-a variability, suggesting that the intrusions are important in promoting the local development of phytoplankton. The generation of slope water penetrations at this location may be triggered by the inshore excursion of the 100 m isobath, which appears to steer the Malvinas Current waters over the outer shelf. Fil: Piola, Alberto Ricardo. Ministerio de Defensa. Armada Argentina. Servicio de Hidrografía Naval. Departamento Oceanografía; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ciencias de la Atmósfera y los Océanos; Argentina Fil: Martínez Avellaneda, N. Universitat Hamburg; Alemania Fil: Guerrero, Raul Alfredo. Instituto Nacional de Investigaciones y Desarrollo Pesquero; Argentina Fil: Jardón, F. P. Universite de Paris VI; Francia Fil: Palma, Elbio Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Argentino de Oceanografía. Universidad Nacional del Sur. Instituto Argentino de Oceanografía; Argentina. Universidad Nacional del Sur. Departamento de Física; Argentina Fil: ...